An XML schema representation for the communication design of electronic negotiations - Strobel, Michael (Computer networks (Amsterdam, Netherlands : 1999), 2002)
Support for negotiations in electronic markets is an important issue in today's e-commerce research. However, only few efforts address the design of electronic negotiations e.g., the sequence of actions or obligations of the negotiating parties. An explicit negotiation design can also address the ontology problem of electronic negotiations: how to ensure that the negotiating parties have the same understanding regarding the issues that are subject to the negotiation. This paper proposes a communication design for electronic negotiations that specifies the common syntax and semantics for the representation of the issues of a negotiation, and suggests XML Schema as the run-time format and validation mechanism for this communication design.